CX3CR1 Acts as a Protective Biomarker in the Tumor Microenvironment of Colorectal Cancer - Yue, Yuanyi; Zhang, Qiang; Sun, Zhengrong (Frontiers in Immunology, 2022)
Tumor microenvironment (TME) plays an important role in the pathogenesis of many cancers. We aimed to screen the TME-related hub genes of colorectal adenoma (CRAD) and identify possible prognostic biomarkers. The gene expression profiles and clinical data of 464 CRAD patients in TCGA database were downloaded. The Estimation of Stromal and Immune cells in Malignant Tumours using Expression data (ESTIMATE) algorithm was performed to calculate the ImmuneScore, StromalScore, and EstimateScore. Thereafter, differentially expressed genes (DEGs) were screened. Gene ontology (GO), KEGG pathway and protein-protein interaction (PPI) analysis were performed to explore the roles of DEGs. Furthermore, univariate and multivariate Cox analyses were accomplished to identify independent prognostic factors of CRAD. CX3CR1 was selected as a hub gene and the expression was confirmed in colorectal cancer (CRC) patients and cell lines. The correlations between CX3CR1 and tumor immune infiltrating cells were estimated by Tumor Immune Estimation Resource database (TIMER) and CIBERSORT analysis. Besides, we investigated the effects of co-culture with THP-1-derived macrophages with HCT8 cells with low CX3CR1 expression on immune marker expression, cell viability and migration. There were significant differences in the ImmuneScore and EstimateScore among different stages. Patients with the low-scores presented significantly lower lifetimes than the high-scores group. Moreover, we recognized 1578 intersection genes in ImmuneScore and StromalScore, and these genes were mainly enriched in numerous immune-related biological processes. CX3CR1 was found to be associated with immune cell infiltration levels, immune marker expression and macrophage polarization. Simultaneous silencing of CX3CR1 and co-culture with THP-1 cells further regulated macrophage polarization and promoted the cell proliferation and migration of CRC cancer cells. CX3CR1 was decreased in CRAD tissues and cell lines and was related to T and N stages, tumor differentiation, and prognosis. Our results suggest that CX3CR1 contributes to the recruitment and regulation of immune inﬁltrating cells and macrophage polarization in CRC and TAM-induced CRC progression. CX3CR1 may act as a prognostic biomarker in CRC.